1998
DOI: 10.1002/(sici)1097-4547(19980301)51:5<627::aid-jnr10>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of nitric oxide synthase activity upon oxidative stress in cultured retinal cells

Abstract: In the present study we examined the effect of oxidative stress-mediated hydroperoxide formation on the activity of nitric oxide synthase (NOS) in retinal cells in culture. Oxidative stress was induced in the presence of Fe2+ and ascorbate or Fe2+ alone and compared to H2O2-induced maximal cellular oxidation, and was measured by following the formation of intracellular hydroperoxides with the probe DCFH2 (2',7'-dichlorodihydrofluorescein). After a 15-min exposure to the oxidants, formation of hydroperoxides wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Moreover, NOS inhibitors protected against excitotoxic neuronal injury [43]. Although we found previously that nitro G -w-arginine reduced the activity of NOS in retinal cells in culture [29], exposure to nitro G -w-arginine was not effective against retinal cell injury up to 12 h upon chemical ischemia, hypoglycemia or oxidative stress ( Table 1). The failure of nitro G -warginine to increase the viability of retinal cells upon hypoglycemia or ischemia may also be related with a reduced involvement of the NMDA receptors in cell injury (Table 1), because the generation of nitric oxide has been implicated in the excitotoxic neuronal injury mediated by activation of the NMDA receptors [43,44].…”
Section: Mk-801 Nitrendipine and Nitro G -W-arginine May Not Be Highmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, NOS inhibitors protected against excitotoxic neuronal injury [43]. Although we found previously that nitro G -w-arginine reduced the activity of NOS in retinal cells in culture [29], exposure to nitro G -w-arginine was not effective against retinal cell injury up to 12 h upon chemical ischemia, hypoglycemia or oxidative stress ( Table 1). The failure of nitro G -warginine to increase the viability of retinal cells upon hypoglycemia or ischemia may also be related with a reduced involvement of the NMDA receptors in cell injury (Table 1), because the generation of nitric oxide has been implicated in the excitotoxic neuronal injury mediated by activation of the NMDA receptors [43,44].…”
Section: Mk-801 Nitrendipine and Nitro G -W-arginine May Not Be Highmentioning
confidence: 83%
“…By using nitrendipine [Ca 2ϩ ] i changes, in response to activation of ionotropic glutamate receptors [27] or upon K ϩ -depolarization [28], were previously shown to involve the L-type Ca 2ϩ channels in retinal cells in culture. Furthermore, we showed that nitro G -w-arginine decreased the activity of NOS in retinal cells in culture [29] by decreasing the conversion of citrulline from arginine. Nevertheless, retinal cell injury induced by oxidative stress, chemical ischemia or hypoglycemia was not significantly affected after incubation with MK-801, nitrendipine or nitro G -w-arginine ( Na ϩ medium without Mg 2ϩ , but containing Ca 2ϩ , for 15 min plus 12 h postincubation, did not influence significantly the release of LDH (not shown).…”
Section: Effect Of Mk-801 Nitrendipine and Nitro G -W-arginine On Rementioning
confidence: 87%
See 1 more Smart Citation
“…2008), and DCF fluorescence were measured in retinal cells using a spectrometer (e.g. Rego and Oliveira 1998; Cacicedo et al. 2005), but not the combination of time‐lapse in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of intracellular pH (pHi) was assessed by following the changes in fluorescence of the pH-sensitive probe 2V,7V-bis-(carboxyethyl)-5(and-6)carboxyfluorescein (BCECF) similarly as described by Rego and Oliveira (1998). Cortical cells were loaded with 5 AM BCECF-AM for 45 min, at 378C, in culture medium, in an atmosphere of 95% air and 5% CO 2 , to avoid major changes in cellular pH.…”
Section: Intracellular Ph Measurementsmentioning
confidence: 99%